Mayo Clinic on Healthy Aging - Creagan, Edward (Estados Unidos: Mayo Clinic Heallth, 2001)
Contiene información como llevar una buena salud y así evitar enfermedades futuras
CONTENIDO Chapter 1. Facts and phases Chapter 2. Your body Chapter 3. Your Mind Chapter 4. Your Spirit Chapter 5 Your finances y otros ...
Incluye índice
Keywords: SALUD -- PREVENCIÓN